Penerapan Model Problem Based Learning dengan Media Powerpoint untuk Meningkatkan Motivasi Belajar Siswa - Desy Nursitowati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The problem in this research is the low learning motivation of Grade 1 students at SD Negeri Pilang 1 Masaran in thematic learning. This is because the learning system provided by the teacher in the class is monotonous and less interesting, causing students to be less enthusiastic about taking lessons. This research was conducted with the aim of increasing the learning motivation of grade 1 students at SD Negeri Pilang 1 Masaran in Thematic learning using powerpoint media. This research method is Classroom Action Research which consists of 2 cycles and each cycle consists of 4 stages, namely planning, implementing, observing, and reflecting. Data collection techniques using observation, questionnaires and documentation. Data analysis techniques were carried out qualitatively and quantitatively using the percentage formula (%) questionnaire data to see the successful application of the use of PowerPoint media and problem based learning models in the classroom in order to increase student learning motivation. Based on the results of observations of teacher activity in using powerpoint media with the problem based learning model in Cycle I, it was obtained that students' motivation data had increased. Increased learning motivation greatly affects student learning outcomes. The percentage of students' learning motivation in the high category in cycle I was 62% or 15 students and students in the medium category were 37% or 9 students. The learning process in cycle II further enhances students' understanding of the material. An increase in student learning motivation was shown by students in the high category reaching 79% or 19 students and being in the moderate category 21% or 5 students. Based on the research results obtained, it can be concluded that the application of learning using powerpoint media with problem based learning models in thematic learning can increase students' learning motivation in the learning process at school.